2002
DOI: 10.1044/cicsd_29_f_132
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress in Speech-Language Pathologists Working in Rural, Suburban, and Urban Schools: Social Support and Frequency of Interactions

Abstract: Job stress levels of speech-language pathologists (SLPs) working in rural, suburban, and urban schools were determined using a standardized inventory. The majority of SLPs (82%) rated their overall job stress levels with an overall judgement score of "barely noticeable." However, there were a variety of items that surfaced as chronic stressors for SLPs. The top stress items included overwhelming paperwork (82%), overwork (71%), lack of time (64%), lack of preparation time (62%), and large caseload size (55%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Clinicians therefore appeared to have adequate levels of control over occupational demands, resulting in low levels of stress around autonomy. Similarly, a lack of control over service delivery was not reported as a stressor for the school-based SLPs in Blood et al's (2002c) study, in which stress was "barely noticeable". Kaegi et al, (2002) found that the large majority of SLPs in their study had "enough authority to do their job" whereas, while interviewing clinicians, McLaughlin et al (2008) identified stress in SLPs that was due to a lack of autonomy.…”
Section: Control/autonomymentioning
confidence: 63%
See 2 more Smart Citations
“…Clinicians therefore appeared to have adequate levels of control over occupational demands, resulting in low levels of stress around autonomy. Similarly, a lack of control over service delivery was not reported as a stressor for the school-based SLPs in Blood et al's (2002c) study, in which stress was "barely noticeable". Kaegi et al, (2002) found that the large majority of SLPs in their study had "enough authority to do their job" whereas, while interviewing clinicians, McLaughlin et al (2008) identified stress in SLPs that was due to a lack of autonomy.…”
Section: Control/autonomymentioning
confidence: 63%
“…Hutchins, et al (2010) reported that while SLPs were generally satisfied with their jobs, there was a significant relationship between caseload size and workload satisfaction specifically. The perception of a high caseload was associated with increased stress in Harris et al's study in 2009;and Blood, et al, (2002c) described overwork and large caseloads as "chronic" stressors for school-based SLPs. However, Blood et al (2002a) found no statistical relationship between caseload size and stress.…”
Section: Workload And/or Caseload Sizementioning
confidence: 96%
See 1 more Smart Citation
“…The barriers identified can limit rural and remote consumers’ usage of health services, indicating a possible inequity if compared to larger, more accessible urban areas (Callaghan et al, 2005). Even if access to personnel is available in a rural setting, it has been shown that rural personnel are slightly less experienced than their urban counterparts (Blood et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wilson, 2005). Even if access to a speech-language pathologist is available in a rural setting, it has been shown that rural personnel are slightly less experienced than their urban counterparts (Blood, Thomas, Ridenour, & Hammer, 2002). With these issues considered and the fact that clefting is a low incidence birth anomaly, it is more likely that the family of a child with CL/P who is born in a rural hospital may not have access to initial parent feeding instruction and education.…”
Section: Rural Healthcarementioning
confidence: 99%